The effective factors on health tourism marketing in hospitals affiliated to Iran University of Medical Sciences - Seyed Ahmad Ahmadi; Seyed Mohammad Mahdi Paknejad rizi; Pouran Raeissi (Tehran University of Medical Sciences, 2022)
Introduction: Health tourism is a new form of tourism industry that aims to maintain recovery and regain physical and mental health and has grown in recent years. Therefore, the present study was conducted to investigate the factors affecting the marketing of health tourism in hospitals affiliated to Iran University of Medical Sciences. Methods: The present study is descriptive-analytical and was conducted on 270 individuals at some point in 2021. The study population consisted of all heads, managers, matrons, quality managers and heads of international patients of public and private hospitals affiliated to Iran University of Medical Sciences. The data collection tool was a researcher-made questionnaire. Data were analyzed by using SPSS software version 23. Results: The results of study showed a significant difference between the components of price, place, promotion and people in the two types of hospitals (P-value <0.05). While no significant difference was observed between other components (product, physical evidence and process) (P-value <0.05). Conclusion: Providing the needs of medical tourists will increase their satisfaction. Therefore, paying attention to the effective factors in marketing and trying to solve the shortcomings of this field can be very effective in attracting health tourists and turning Iran into a medical tourist destination.